2021
DOI: 10.1002/jcb.29933
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of prolyl hydroxylase inhibitor by per‐residue energy decomposition‐based pharmacophore approach

Abstract: Hypoxia is an effective preconditioning stimulus and many cellular responses to hypoxia are mediated through a transcription control complex termed the hypoxia‐inducible factor (HIF). The stability and activation of HIF are governed by HIF prolyl‐4‐hydroxylases 2 (PHD2). Hence, the development of a small molecule inhibitor for prolyl hydroxylase has been suggested as a potentially useful therapeutic strategy for the treatment of oxidative/ischemic stress conditions. Thus, to unveil a novel human PHD2 inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Peonidin (2-(4-hydroxy-3-methoxyphenyl) chromenylium-3,5,7-triol) exhibited the best binding conformations with the lowest binding energy values with bacterial (− 8.2 kcal/mol), fungal (− 8.2 kcal/mol) target proteins (Tables 5 and 6 ). Our findings are supported by a previous study that showed that the lower the binding energy score, the better the protein–ligand binding stability was identified 44 . The peonidin formed the most excellent ligand–protein complexes with six tested microbial target proteins compared with other compounds.…”
Section: Resultssupporting
confidence: 91%
“…Peonidin (2-(4-hydroxy-3-methoxyphenyl) chromenylium-3,5,7-triol) exhibited the best binding conformations with the lowest binding energy values with bacterial (− 8.2 kcal/mol), fungal (− 8.2 kcal/mol) target proteins (Tables 5 and 6 ). Our findings are supported by a previous study that showed that the lower the binding energy score, the better the protein–ligand binding stability was identified 44 . The peonidin formed the most excellent ligand–protein complexes with six tested microbial target proteins compared with other compounds.…”
Section: Resultssupporting
confidence: 91%
“…Many studies have used the MD simulation approach to investigate ligand binding with proteins [ 7 , 19 , 20 , 21 ]. All-atom MD simulations were carried out for the docked complex of HSA–HpzA and compared with those for the free state of HSA.…”
Section: Resultsmentioning
confidence: 99%
“…The solvent-accessible surface area (SASA) of a protein is the surface area accessible to its adjacent solvent [ 19 ]. The stability and folding behavior of proteins are studied using SASA [ 20 ].…”
Section: Resultsmentioning
confidence: 99%